PENGARUH GOODWILL DAN INTELLECTUAL CAPITAL TERHADAP NILAI PASAR DAN KINERJA KEUANGAN PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017 – 2019) - Marlina Marlina; Kamaliah Kamaliah; Hariyani Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine and analyze the effect of goodwill and intellectual capital on the market value and financial performance of companies listed on the Indonesia Stock Exchange in 2017-2019. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sample selection method was carried out by purposive sampling, namely the method of selecting samples with certain criteria. Samples that meet the criteria are 39 companies with an observation period of 3 years, so the number of samples to be studied is 117 companies. The data analysis used multiple linear regression. The results show that goodwill (X1) has an effect on market value (Y1) with a significance value of 0.019 < 0.05. Goodwill (X1) has an effect on the company's financial performance (Y2) with a significance value of 0.003 < 0.05. Intellectual capital (X2) has an effect on market value (X1) with a significance value of 0.038 <0.05. While intellectual capital (X2) has no effect on the company's financial performance (Y2) with a significance value of 0.236 > 0.05.Keywords: Goodwill, Intellectual Capital, Market Value, and Company Financial Performance